2014
DOI: 10.1042/bj20140423
|View full text |Cite
|
Sign up to set email alerts
|

Impaired selenoprotein expression in brain triggers striatal neuronal loss leading to co-ordination defects in mice

Abstract: Selenocysteine Insertion Sequence (SECIS)-Binding Protein 2 (Secisbp2) binds to SECIS elements located in the 3′-untranslated region of eukaryotic selenoprotein mRNAs. It facilitates incorporation of the rare amino acid selenocysteine in response to UGA codons. Inactivation of Secisbp2 in hepatocytes greatly reduced selenoprotein levels. Neuron-specific inactivation of Secisbp2 (CamK-Cre; Secisbp2fl/fl) reduced cerebral expression of selenoproteins to a lesser extent than inactivation of tRNA[Ser]Sec. This all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 39 publications
1
42
0
1
Order By: Relevance
“…To further analyze SBP2 function in organs not accessible in patients, mice models have been developed. While gene inactivation leads to embryonic lethality (123), the conditional deletion of SBP2 is less detrimental than Sec-tRNA [Ser]Sec inactivation and provides a tool for further in vivo functional analysis (124).…”
Section: The Secis Binding Protein 2 (Sbp2)mentioning
confidence: 99%
“…To further analyze SBP2 function in organs not accessible in patients, mice models have been developed. While gene inactivation leads to embryonic lethality (123), the conditional deletion of SBP2 is less detrimental than Sec-tRNA [Ser]Sec inactivation and provides a tool for further in vivo functional analysis (124).…”
Section: The Secis Binding Protein 2 (Sbp2)mentioning
confidence: 99%
“…Although not directly comparable, it was previously shown that the reduction of SBP2 in cultured cells by shRNA treatment resulted in a very different pattern of mRNA changes (Squires et al 2007), suggesting that there may exist cell-type specific regulatory networks. Similarly, the brain-specific reduction of SBP2 in mice showed a unique pattern of selenoprotein mRNA concentrations, further implicating SBP2 in regulating mRNA abundance (Seeher et al 2014a). Overall, the striking finding from these studies is the number of selenoprotein mRNAs that are unaffected by the lack of translation.…”
Section: 3 Interplay With Nonsense Mediated Decay (Nmd)mentioning
confidence: 99%
“…Previous studies have shown that Se has an important biochemical function in erythrocyte glutathione peroxidase activity (GSH-Px) [1,2]. Se promotes proper gait [3], healthy pregnancies [4,5], and growth [6,7] in animals. Its deficiency can cause nutritional and metabolic diseases [8,9] and can affect the immune system [10,11].…”
Section: Introductionmentioning
confidence: 99%